Elastically confined martensitic transformation at the nano-scale in a multifunctional titanium alloy. (15th August 2017) - Wang, H.L.; Hao, Y.L.; He, S.Y.; Li, T.; Cairney, J.M.; Wang, Y.D.; Wang, Y.; Obbard, E.G.; Prima, F.; Du, K.; Li, S.J.; Yang, R.
Abstract: A martensitic transformation (MT) is a typical first-order diffusionless crystal structural change with strong autocatalysis like avalanche at a speed of sound propagation. This unique characteristic, however, is undetectable in some multifunctional titanium alloys. Recently, a nano-scale elastically confined MT mechanism was proposed because a nano-scale Nb modulation in a Ti-Nb based alloy was observed. Here we analyze the elastic confinement in details and its induced novel properties in a wide temperature range. The statistical analyses of atom probe tomography (APT) data confirm the existence of the nano-scale Nb concentration modulation. The synchrotron X-ray diffraction (SXRD) profiles demonstrate that the nano-scale Nb modulation causes weak diffuse scattering, as evidenced by the extreme broad diffraction bands. The tensile tests find a critical temperature of ∼150 K, where the critical stress to induce the MT and Young's modulus reach the minimum and the superelastic strain reaches the maximum (∼4.5%) and keeps constant as the temperature decreases further to <4.2 K. To reveal these abnormal behaviors of the MT, the Born criterion governing the elastic stability of cubic crystal is modified by introducing an elastic confinement term and a new Clausius-Clapeyron relationship is established to evaluate the elastically confined MT. The results are consistent with the experimental findings, including the solely stress-induced (no thermally induced) reversibility. Graphical abstract: Image